Profiles of Killer Systems and Volatile Organic Compounds of Rowanberry and Rosehip-Inhabiting Yeasts Substantiate Implications for Biocontrol - Iglė Vepštaitė-Monstavičė; Juliana Lukša-Žebelovič; Violeta Apšegaitė; Raimondas Mozūraitis; Robertas Lisicinas; Ramunė Stanevičienė; Laima Blažytė-Čereškienė; Saulius Serva; Elena Servienė (Foods)
Yeasts produce numerous antimicrobial agents such as killer toxins, volatile organic compounds (VOCs), and other secondary metabolites, establishing themselves in developing natural and sustainable biocontrol strategies for agriculture and food preservation. This study addressed the biocontrol potential of yeasts, isolated from spontaneous fermentations of rosehips (Rosa canina L.) and rowanberries (Sorbus aucuparia L.), focusing on their killer phenotypes and VOCs production. Yeasts were isolated using spontaneous fermentations with Hanseniaspora uvarum and Metschnikowia pulcherrima identified as the dominant species, comprising approximately 70% of the yeast population. Among 163 isolated strains, 20% demonstrated killing activity, with Saccharomyces cerevisiae exhibiting the strongest killing efficiency, as well as Pichia anomala and M. pulcherrima showing broad-spectrum antagonistic activity. This study identified dsRNA-encoded killer phenotypes in S. cerevisiae, S. paradoxus, and Torulaspora delbrueckii, revealing multiple distinct killer toxin types. The biocontrol potential of wild berry-inhabiting yeasts was demonstrated in a real food system, grape juice, where the S. cerevisiae K2-type killer strain significantly reduced fungal contaminants. The selected H. uvarum, M. pulcherrima, S. cerevisiae, and S. paradoxus yeast strains representing both berries were applied for VOC analysis and identification by gas chromatography-linked mass spectrometry. It was revealed that the patterns of emitted volatiles are yeast species-specific. Statistically significant differences between the individual VOCs were observed among killing phenotype-possessing vs. non-killer S. paradoxus yeasts, thus revealing the involvement of killer systems in multi-level biocontrol enablement. The performed studies deepen our understanding of potential yeast biocontrol mechanisms, highlight the importance of produced antimicrobials and volatiles in ensuring antagonistic efficacy, and prove the relevance of isolated biocontrol yeasts for improving food safety.